367 - Mise en oeuvre de la résolution IICA/JIA/Res.382 (XI-O/01) Évaluation du programme de protection sanitaire agricole et d'innocuité des aliments de l'IICA - Comité Exécutif (CE) (2017)
(WD-407) Evaluation of IICA's Agricultural Health and Food Safety Program: The Multiple Roles of Agricultural Health and Food Safety: Bases for Evaluation and for the Orientation of IICA´s Action